Feasibility and constraints of particle targeting using the antigen-antibody interaction - Tokárová, Viola; Pittermannová, Anna; Král, Vlastimil; Řezáčová, Pavlína; Štěpánek, František (Nanoscale, 2013)
This work is concerned with the surface modification of fluorescent silica nanoparticles by a monoclonal antibody (M75) and the specific bioadhesion of such particles to surfaces containing the PG domain of carbonic anhydrase IX (CA IX), which is a trans-membrane protein specifically expressed on the surfaces of several tumor cell lines. The adhesion strength of antibody-bearing silica nanoparticles to antigen-bearing surfaces was investigated under laminar flow conditions in a microfluidic cell and compared to the adhesion of unmodified silica nanoparticles and nanoparticles coupled with an unspecific antibody. Adhesion to cancer cells using flow cytometry was also investigated and in all cases the adhesion strength of M75-modified nanoparticles was significantly stronger than for the unmodified or unspecific nanoparticles, up to several orders of magnitude in some cases. The specific modification of nano- and microparticles by an antibody-like protein therefore appears to be a feasible approach for the targeting of tumor cells.
Keywords: imunokomplex; Nanoparticles; Humans; povrchové vlastnosti; Microscopy, Confocal; Carbonic Anhydrase IX; mikrofluidní analytické techniky; Microfluidic Analytical Techniques; Antibodies, Monoclonal; Silicon Dioxide; konfokální mikroskopie; Cell Adhesion; karboanhydrasa IX; lidé; zvířata; myši; Antigens, Neoplasm; buňky NIH 3T3; Mice; karboanhydrasy; antigeny nádorové; NIH 3T3 Cells; Antigen-Antibody Complex; nanočástice; oxid křemičitý; monoklonální protilátky; nádorové buněčné linie; Animals; buněčná adheze; Cell Line, Tumor; terciární struktura proteinů; Protein Structure, Tertiary; Carbonic Anhydrases; Surface Properties